Evaluasi Supervisi Pendidikan dalam Meningkatkan Mutu Pendidikan - Khalib Gadafi; Afdhal Surya Hamid; Muhammad Haikal; Ahmad Sabri; Yusran Lubis (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
In this article, the conceptual basis of educational supervision programme evaluation management will be explained. To improve the quality of education, management of educational supervision programme evaluation is important. It will provide a unique evaluation of education. In this explanation, the reasons why education supervision programme evaluation management is essential, the objectives of programme evaluation, the principles underlying evaluation and the procedures used to conduct evaluation are discussed. To improve evaluation management, a conceptual foundation is needed to understand education supervision programme evaluation on a micro and macro scale to improve the quality of education.